2022
DOI: 10.3389/fendo.2022.901760
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Diagnosis of Catecholamine-Producing Tumors of Childhood: Neuroblastoma, Pheochromocytoma and Paraganglioma

Abstract: Catecholamine-producing tumors of childhood include most notably neuroblastoma, but also pheochromocytoma and paraganglioma (PPGL). Diagnosis of the former depends largely on biopsy-dependent histopathology, but this is contraindicated in PPGL where diagnosis depends crucially on biochemical tests of catecholamine excess. Such tests retain some importance in neuroblastoma though continue to largely rely on measurements of homovanillic acid (HVA) and vanillylmandelic acid (VMA), which are no longer recommended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…Neuroendocrine neoplasms encompass a large diversity of epithelial and non-epithelial neoplasms differing for their incidence, localization, morphology, biology and available treatments. Despite these facts, these tumors share common characteristics, including the potential ability of hormones and biogenic amine production and secretion (1)(2)(3)(4). Pheochromocytoma (PHEO), paraganglioma (PGL) and neuroblastoma (NB) are non-epithelial neuroendocrine neoplasms arising from the adrenal medulla and ganglia of the sympathetic nervous system (SNS), which typically produce and secrete catecholamines (CATs; dopamine, DA, norepinephrine NE, epinephrine, E) (5).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroendocrine neoplasms encompass a large diversity of epithelial and non-epithelial neoplasms differing for their incidence, localization, morphology, biology and available treatments. Despite these facts, these tumors share common characteristics, including the potential ability of hormones and biogenic amine production and secretion (1)(2)(3)(4). Pheochromocytoma (PHEO), paraganglioma (PGL) and neuroblastoma (NB) are non-epithelial neuroendocrine neoplasms arising from the adrenal medulla and ganglia of the sympathetic nervous system (SNS), which typically produce and secrete catecholamines (CATs; dopamine, DA, norepinephrine NE, epinephrine, E) (5).…”
Section: Introductionmentioning
confidence: 99%
“…In human adult β cells, dopamine has been found to decrease insulin secretion via dopamine type 2 receptors . Measurement of 3-methoxytyramine, a primary metabolite of dopamine, has been shown to increase the diagnostic sensitivity to detect catecholamine-producing tumors . Furthermore, in patients with elevated metanephrine and normetanephrine concentrations, an association with increased 3-methoxytyramine has been reported .…”
Section: Discussionmentioning
confidence: 99%
“…At present, age of onset, INSS stage, histological type, degree of differentiation, and MYCN gene ampli cation have been recognized as risk factors for NB [14,15] . Urinary VMA and HVA levels, serum Fer, NSE, and LDH levels are considered to be characteristic tumor markers of NB, and these parameters are helpful for the initial diagnosis, therapeutic evaluation, and monitoring of the recurrence of NB [16,17] . In this study, age, INSS stage, Fer, NSE, and LDH were analyzed, and the results showed that all the above indicators were associated with the prognosis of NB.…”
Section: Discussionmentioning
confidence: 99%